2011
DOI: 10.1007/s11325-011-0608-8
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnography reveals unexpectedly high rates of organic sleep disorders in patients with prediagnosed primary insomnia

Abstract: Indications for a PSG should be handled less restrictively in the diagnostic workup of older insomnia patients since they have a higher risk of comorbid sleep disorders even in the absence of the clinical signs of SAS or PLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 22 publications
0
16
0
5
Order By: Relevance
“…14 The co-occurrence of occult SDB (i.e., SDB that is present but has not been diagnosed with a sleep study) in the context of insomnia was examined in a study of patients initiating insomnia the rapy. 15 This study found that 27% of patients had occult SDB and that patients with SDB were older and had a higher body mass 15 Another study found that 29% of older individuals recruited for an insomnia study had occult SDB. 11 Although older veterans are at high risk for both occult SDB and insomnia, the prevalence of occult SDB among older veterans with insomnia has not been reported, to our knowledge.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 90%
“…14 The co-occurrence of occult SDB (i.e., SDB that is present but has not been diagnosed with a sleep study) in the context of insomnia was examined in a study of patients initiating insomnia the rapy. 15 This study found that 27% of patients had occult SDB and that patients with SDB were older and had a higher body mass 15 Another study found that 29% of older individuals recruited for an insomnia study had occult SDB. 11 Although older veterans are at high risk for both occult SDB and insomnia, the prevalence of occult SDB among older veterans with insomnia has not been reported, to our knowledge.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 90%
“…Overall, our data suggest that polysomnography is useful to assess comorbid sleep disorders and OSA in particular in PD patients. 35 However, PSG cannot explain subjective symptoms of sleepiness and insomnia specific to PD. The MSLTs did not reflect subjective daytime sleepiness as measured by the ESS.…”
Section: Discussionmentioning
confidence: 99%
“…65 Cronlein and colleagues found that occult OSA was most likely to be found on PSG in older and overweight individuals with insomnia, alluding to the possible necessity for PSG in these patients. 66 Men with insomnia who frequently reported dry mouths were likely to have occult sleep apnea even after been screened for possible OSA. 67 Our findings complement these studies by highlighting the risks of occult OSA in insomnia patients, and this might be particularly prominent in those with the MI symptom profile.…”
Section: "Mild Insomnia" Symptom Cluster Profilementioning
confidence: 99%